The Translation of Multimedia News Stories: Rewriting the Digital Narrative. - Hernández-Guerrero, María José (Sage, 2022)
This article presents a case study that examines the translation of multimedia news stories, a journalistic narrative that presents news using two or more media formats, such as spoken and written word, moving and still images or graphics, including interactive and hypertextual elements. The research focuses on the news reports of the digital newspaper Theguardian.com which is translated by Eldiario.es, a digital Spanish newspaper. Drawing on a corpus of 30 pairs (of English and Spanish versions), I explore the strategies used by journalists in preparing the multimedia news story for its new audience. The methodology used combines comparative content analysis with a semi-standardised interview with the head of the International section of Eldiario.es. Translated news reports are respectful of the original written content from Theguardian.com but they replace multimedia content with other, different, content. The discursive effects of these substitutions are discussed and the reasons underlying these changes are analysed. The findings suggest that substitution of hypermedia content facilitates intercultural circulation of the multimedia journalistic narrative, but the modification of these contents on the part of the target medium produces its own range of effects.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/9362
Keywords: Periodismo - Traducción; Traducción - Aspectos sociales; Traducción periodística; Journalistic translation